Analyzing Lived Experiences of Athlete and Coach Relationships in Sports - Eko Purnomo; Nina Jermaina; Alzet Rama; Nor Eeza Binti Zainal Abidin (OVS LLC, 2024)
Objectives. The two main stressors affecting athletes' wellbeing are relationships between coaches and athletes and social support. This study aims to investigate the connections between athletes' psychological health, social support, and coach-athlete interactions. Relationships between coaches and athletes have a favorable impact on future coaching techniques and support systems, which in turn improves athlete wellbeing. Materials and methods. This study employed a quantitative approach using survey methods. The study involved 323 respondents consisting of 231 males (71.52%) and 92 females (28.48%). The instrument used in this study was the Instructor-Student Rapport Scale, comprising 2 dimensions (pleasant interactions and personal relationships). The study results were analyzed using the t-test to determine the significance of differences in athletes' life experiences based on their relationship with the coach. The findings of the study explain that the experiences of athletes' gender have differences regarding the relationship with the coach. Results. This result has also been proven by the results of the t test calculation of <0.001. Meanwhile, the results of t test calculations related to the type of sport (individual and group) obtained results > 0.001, which states that there is no difference in life experience between athletes and coaches. Conclusions. These findings lead to the conclusion that the most crucial factor in facilitating and enabling meaningful life experiences between coaches and athletes is the coach's proximity to the athletes.